Pengaruh Pengembangan, Kualitas Pelayanan Produk Terhadap Minat Anggota Untuk Menggunakan Produk Simpanan Pada KSPPS BMT UGT Nusantara - Wildan Faizul Mubarok; Abdussalam (CV. ITTC INDONESIA, 2023)
This research aims to test the influence of development and product service quality on members' interest in using savings products at KSPPS BMT UGT Sidogiri. In this study, the independent variable is development and product service quality, while the dependent variable in this research is members' interest in using savings products. The population in this research are several members of KSPPS BMT UGT Sidogiri with a total of 150 members, with a sample of 15 respondents, with sampling using a simple random sampling method. This type of research uses quantitative methods and primary data taken from respondents' answers to statements. From the questionnaire distributed using Google Forms. The data analysis technique in this research uses validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, f-tests, and coefficient of determination. The results of this research can conclude that the development and quality of product services have a significant effect on members' interest in using savings products at KSPPS BMT UGT Sidogiri.